2017
DOI: 10.1007/s42106-017-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Potential Sites for Rice Cultivation Through Multi-Criteria Evaluation (MCE) Using Remote Sensing and GIS

Abstract: Punjab, Pakistan is famous for rice production in all over the world, but economic indicators are low toward rice contribution in the regional economy. Climatic and physical factors are responsible for rice yield degradation. Suitable land for rice cultivation can be mapped keeping in view these climatic and physical factors. In this research, rice cultivation season was calculated using Moderate Resolution Imaging Spectro-radiometer (MODIS) time series datasets for the complete year 2014. Landsat 8 thermal da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…These ranges were 0.16-0.2%, 0.4-0.48%, 0.69-0.73% and 0.85-0.90% of the CASA based yield, respectively. To investigate further, an interpolated map was developed based on actual yield levels, as shown in Figure 14, and it was compared with soil suitability zones delineated by Hassan et al, 2018 [108]. We observed that the lowest yield of 414 kg/ha (0.16% of the CASA based yield) was obtained from areas which were not suitable for rice cultivation with pH > 8.4, electric conductivity (EC) of 1.75-2.25 and excessively drained soil type (ST).…”
Section: Development Of Soil Suitability Constant (Hα)mentioning
confidence: 99%
See 2 more Smart Citations
“…These ranges were 0.16-0.2%, 0.4-0.48%, 0.69-0.73% and 0.85-0.90% of the CASA based yield, respectively. To investigate further, an interpolated map was developed based on actual yield levels, as shown in Figure 14, and it was compared with soil suitability zones delineated by Hassan et al, 2018 [108]. We observed that the lowest yield of 414 kg/ha (0.16% of the CASA based yield) was obtained from areas which were not suitable for rice cultivation with pH > 8.4, electric conductivity (EC) of 1.75-2.25 and excessively drained soil type (ST).…”
Section: Development Of Soil Suitability Constant (Hα)mentioning
confidence: 99%
“…We further superimposed the spatial distribution of rice cultivation to yield a variability map (already compared with soil suitability zones), [108] and found that the farmers had planted rice in…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have used a set of powerful tools embedded in Arc GIS to compute various variables e.g. temperature, pressure, rainfall, humidity, soil pH, soil types and soil electric conductivity which effected the productivity [8,9]. Multi Criteria Evaluation (MCE) techniques are widely used to analyze the suitable sites which assist in decision making of a particular problem [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid urbanization and the population growth, have increased the demands of fresh water for consumption at domestic level [1]. The enhanced cycle of various human activities like agriculture, urbanization, and industrialization have put huge pressure on available reservoirs of fresh water.…”
mentioning
confidence: 99%